Regional Dynamics in the High Quebradas of the Valle Calchaquí Medio (Salta, Argentina) Between the Eleventh and Early Seventeenth Centuries - (:unkn) unknown (Springer, 2018)
For the Northwestern Argentina (NWA) between AD 1000 and 1430, theproposed situation encompasses the existence of a state of political fragmentation, conflict situations, and the emergence of hierarchies materialized in the presence of defensive settlements or pukaras, iconography, war paraphernalia, and evidences of trauma on human remains, always considering the climatic changes that occurred in the Andes starting in the thirteenth century as one of the causes. The archaeological information from the high ravines of Valle Calchaquí Medio (VCM) located in thecurrent province of Salta, NWA between eleventh and seventeenth centuries,allowed us to hypothesize a continuity in the occupation of this space followinglogics and practices from pre-Hispanic times which were linked to the subsistence and social reproduction, such as seasonal and altitudinal management.

Williams, V. I. (2018). Regional Dynamics in the High Quebradas of the Valle Calchaquí Medio (Salta, Argentina) Between the Eleventh and Early Seventeenth Centuries. En A. Álvarez Larrain y M. C. Greco Mainero (Eds.), Political Landscapes of the Late Intermediate Period in the Southern Andes: the Pukaras and their Hinterlands pp. (131-156). Suiza: Springer.
Fil: Williams, Verónica Isabel. Consejo Nacional de Investigaciones Científicas y Técnicas. Universidad de Buenos Aires. Instituto de las Culturas; Argentina
Keywords: Northwest Argentina; Warfare; Prehispanic Interaction; Subsistence; Social Reproduction